Guided Inquiry-Based Learning to Enhance Elementary School Students’ Participation and Critical Thinking - Lusiana Fernatubun; Marleny Leasa; Johanes Pelamonia; John Rafafy Batlolona (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
Elementary school students’ critical thinking skills remain relatively low, particularly in science learning, which tends to be teacher-centered and emphasizes rote memorization of concepts. This condition results in low student engagement in scientific thinking processes and less optimal learning outcomes. This study aims to analyze the effect of implementing the guided inquiry learning model on students’ scientific critical thinking skills. This research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. The research subjects consisted of 28 fifth-grade students at SD Negeri 38 Ambon, who were divided into an experimental group and a control group. The research instruments included a critical thinking test (pretest and posttest), observation sheets, and documentation. The data were analyzed using normality tests, homogeneity tests, and mean difference tests. The results showed that the average posttest score of critical thinking skills in the experimental group was higher than that of the control group. Statistical testing revealed a significant difference between the two groups, indicating that the implementation of the guided inquiry model had a positive effect on improving students’ critical thinking skills. Guided inquiry learning encourages students to actively engage in observing phenomena, formulating problems, developing hypotheses, conducting investigations, and drawing conclusions based on data. Therefore, it can be concluded that the guided inquiry learning model is effective as an alternative science learning strategy to enhance elementary school students’ critical thinking skills and to create more meaningful, student-centered learning.